The dimensions of the sphenoid sinuses: evaluation before the functional endoscopic sinus surgery - J. Jaworek-Troć; M. Zarzecki; I. Zamojska; J. Iwanaga; W. Przybycień; M. Mazur; R. Chrzan; J. A. Walocha (Folia Morphologica, 2021)
BACKGROUND: The following study aimed to evaluate the dimensions (anteroposterior, transverse and vertical) of the sphenoid sinuses in the adult population. MATERIALS AND METHODS: The study was conducted as a retrospective analysis of the computed tomography (CT) scans of the paranasal sinuses of 296 patients (147 females and 149 males), who did not present any pathology in the sphenoid sinuses. The CT scans of the paranasal sinuses were done with the spiral CT scanner, without using any contrast medium. After obtaining transverse planes, frontal and sagittal planes were created using secondary reconstruction tool. RESULTS: The anteroposterior dimension was found to be 2.65 cm on average, in the range of 0.5–4.3 cm. The transverse dimension was on average 1.98 cm, ranging from 0.5 cm to 4.9 cm. The average vertical dimension was found to be 2.1 cm, in the range of 0.7–3.7 cm. CONCLUSIONS: Due to the high incidence of the anatomical variants of the paranasal sinuses, a CT scan is recommended in all patients before a planned surgery in order to avoid the potential iatrogenic complications. Dimensions of the sphenoid sinuses might point towards more at risk variants, but there is still a substantial amount of research that needs to be done in that aspect.